If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 2k = -10 Solving 2 + 2k = -10 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2k = -10 + -2 Combine like terms: 2 + -2 = 0 0 + 2k = -10 + -2 2k = -10 + -2 Combine like terms: -10 + -2 = -12 2k = -12 Divide each side by '2'. k = -6 Simplifying k = -6
| 2.7a=5.67 | | 80x^3-1250=0 | | 49b^2-182b-56=0 | | 4.2t=10.5 | | -5a+5=0 | | m+8.8=2.7 | | 20+15m=80 | | p+15.3=8.8 | | 1/9(y+18)+1/3(2y+3)=y+3 | | 9(x+7)-6=9-2(x+9) | | -n-2=3 | | 3/5t-1/10t=t-5/2 | | 20m=80 | | -15x+5y=-2 | | 9.9+14.5(12.7-8.4)= | | 29x+40=10x+3 | | 42y-42y= | | 1/3(x-10)+2/4=x/5 | | x+31/2=41/2 | | 20-0.14x=18.32 | | 6(2x+8)=(3x-6) | | 6(9+4x)=-18solve | | 20+14.32=18.32 | | (x^2)+6x+3=0 | | 18+a=-8 | | 8x+6=5+9 | | 20-14.32x=18.32 | | m+7=10 | | -18+a=8 | | 10x^2-85x-45=0 | | (x^3)+(6x^2)+3x-10=0 | | (7x+b)=4(x+2c+b) |